Legal writing - Webley, Lisa (Routledge-Cavendish, 2010)
This comprehensive guide takes students through the legal writing process, from questions to final essays and problem answers. It considers how to dissect essay and problem questions, how to conduct legal research, and how to construct and communicate legal arguments.